THE EFFECT OF TAX EDUCATION, ACCOUNT REPRESENTATIVE (AR) SUPERVISION, OFFICE AUDITS AND TAX ADMINISTRATION SANCTIONS IN THE FORM OF INTEREST ON INDIVIDUAL TAXPAYER COMPLIANCE AT KPP PRATAMA CILEGON FOR THE PERIOD 2017-2021 - Andi; Ginanjar, Seandy; Rosita, Ita (Management Science Research Journal, 2024)
This research is descriptive research which aims to describe a phenomenon or problem that is occurring and developing at this time without the intention of researching it in more depth. This research intends to describe a phenomenon regarding the factors that influence consumer opinions when considering purchasing products through online businesses, such as the influence of price, creation and product reputation. This research intends to describe a phenomenon regarding the factors that influence consumer decisions in purchasing products through online markets, such as the influence of price, creation and product reputation. Based on the results of the analysis, it shows that price has a significant impact on consumer decisions. Higher or lower prices can influence consumers' perceptions of a product's value and ultimately influence their purchasing decisions. Promotions also have a strong influence on consumer decisions. Discounts, coupons and other promotions can encourage consumers to purchase certain products or services. The analysis results also show that there is a complex interaction between price and promotion. Promotions can reduce consumer sensitivity to price, so that higher prices may be more acceptable if accompanied by attractive promotions.